Satisfied but no payment: The impact of perceived value on continuance intention and purchase intention in music streaming services - Kittiporn Sae-tae; Qian Wang (Telematics and Informatics Reports)
The prevalence of digital music streaming has changed the way people listen to music. Over the past few years, digital music has developed, and streaming music over the Internet is a popular way people listen to music. While many reports focus on digital music and music piracy innovations, only a few applications in economic analysis in terms of the customer's willingness to pay for music services should be considered, especially in Thailand, where the country's digital infrastructure has been developing. This study presents the factors influencing perceived value and purchase intention towards music streaming in Thailand with an extended technology acceptance model and a deep understanding of users’ perceived value, satisfaction, and continuance intention in the Thai context. The research investigates future purchase intentions among freemium and premium users, providing a comprehensive view of potential consumer behavior in the music streaming market. The proposed model was empirically evaluated using an online questionnaire-based survey of 443 respondents about the perceived use of music streaming services in Thailand. Structural Equation Modelling (SEM) technique was used to analyze the data. The results indicated that perceived usefulness, perceived ease of use, and perceived enjoyment were directly and positively correlated with perceived value. Besides, perceived value was directly and positively correlated with satisfaction, continuance intention, and purchase intention. Regardless, satisfaction and continuance intention could not predict purchase intention significantly. In the Thai context, consumer satisfaction and continuance intention with music streaming in Thailand are not a good driving factor in suggesting purchase intention. Furthermore, music streaming content, users’ emotional responses, and feelings play a crucial role in the decision to use and subscribe. The results provided further insight into music application market trends and built an understanding of Thai music consumer behavior.